2004
DOI: 10.1111/j.1741-2358.2004.00002.x
|View full text |Cite
|
Sign up to set email alerts
|

Jaw muscles in older overdenture patients

Abstract: The retention of a small number of teeth in the older adult used to support overdentures appears to sustain the CSA of two jaw closing muscles and therefore could enhance these patients' masticatory ability compared with those who were edentulous.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…It was demonstrated that this (Newton et al. ) muscle waste can be impeded when natural roots serve as a stabilisation of an overdenture. Lately, it was demonstrated that placing dental implants could reverse this muscle waste in edentulous elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that this (Newton et al. ) muscle waste can be impeded when natural roots serve as a stabilisation of an overdenture. Lately, it was demonstrated that placing dental implants could reverse this muscle waste in edentulous elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…The masseter is a superficially placed, quadrate muscle, and is well suited for ultrasonographic scanning 3 . The parameters of muscle thickness can be evaluated by using various techniques, such as computed tomography (CT), 4–7 magnetic resonance imaging (MRI), 6,8,9 and ultrasonography 2,6,10–12 . Ultrasonography is an accurate, convenient, easy, and inexpensive method that allows for follow‐up possibilities.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, mandibular ramus shape variation in adults from the Joseon Dynasty population appears to be primarily associated with age‐related changes in muscle strength and bone density but not necessarily directly related to AMTL (Darcey et al, ; Mohammad, Bauer, & Yeh, ; Newton, McManus, & Menhenick, ; Newton, Yemm, Abel, & Menhinick, ; Taguchi, Tanimoto, Suei, & Wada, ). In general, masticatory muscles are weakened and bone density reduces throughout the aging process (Darcey et al, ; Mohammad, Bauer, & Yeh, ; Newton, McManus, & Menhenick, ; Newton, Yemm, Abel, & Menhinick, ; Taguchi, Tanimoto, Suei, & Wada, ). Therefore, mandibular ramus shape may be prone to plasticity throughout the aging process in response to changes in masticatory load caused by relatively weak muscle strength and low bone density.…”
Section: Discussionmentioning
confidence: 99%
“…Although AMTL is generally more likely to occur as individuals age, many archaeological populations show a higher prevalence of AMTL than modern populations due to their more strenuous diets and/or poor oral health (Larsen, ; Mays, ). AMTL impacts masticatory function, by decreasing muscle size (e.g., masseter muscle) and altering mandibular ramus morphology (Mays, ; Newton, McManus, & Menhenick, ; Newton, Yemm, Abel, & Menhinick, ). Specifically, the shape of the mandibular ramus is affected by muscle size decrease and deteriorated masticatory function via changes in the functional occlusion between maxillary and mandibular teeth (Bastir & Rosas, ; Lieberman, ; Singh, ).…”
Section: Introductionmentioning
confidence: 99%